Implementasi Perwali Kota Probolinggo Nomor 173 Tahun 2019 Tentang Pedoman Pengelolaan Anggaran Kelurahan Di Lingkungan Pemerintah Kota Probolinggo - Ayu Kusumaningtyas; Mohammad Natsir (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2024)
Policies related to urban village budgets that began to be implemented in 2019 throughout Indonesia can be categorized as new policies. To implement urban village facilities and infrastructure development activities and community empowerment in urban villages with the urban village budget, the Probolinggo City Government established a policy through Mayor Regulation Number 173 of 2019 concerning Guidelines for Village Budget Management within the Probolinggo City Government. Sukabumi Village, Mayangan District is one of the villages in Probolinggo City that has received village budget allocations. The use of the urban village budget has entered its fifth year of implementation, but there are still infrastructure development activities that have not been carried out repeatedly and other problems that need to be explored and found solutions. This study aims to analyze the implementation of urban village budget management policies and map and analyze what factors are supporting and inhibiting the implementation of village budget management policies based on Probolinggo Mayor Regulation Number 173 of 2019 concerning Guidelines for Village Budget Management in the Probolinggo City Government Environment in Sukabumi Village. The type of research used in this research is descriptive with a qualitative approach with primary data sources through determining informants using purposive sampling and secondary data obtained by observation and documentation methods.